Fasilitas dan Lingkungan Kerja Layanan Kesehatan Terhadap Kepuasan pelanggan - Hermanto, Hermanto; Amani, Tatik; Dwi Vidyastutik, Elok; Herlambang, Tedy (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2019)
Service organizations are required to always optimize the resources to be managed in order to increase customer satisfaction, this study intends to analyze the effect of facilities (direct facilities and supporting facilities) health services and work environment (direct work environment and working environment conditions or weather) health services on customer satisfaction. Retrieval of data with a survey method of 500 respondents of health service users at the Community Health Center in Probolinggo District, with quantitative data methods were analyzed by t test in regression. The results of the study have shown that direct work facilities and supporting facilities as well as the direct work environment of health services have made a positive contribution to customer satisfaction, while the work environment related to environmental conditions or weather as measured by indicators of noise, air pollution, and lighting at the service has not yet fully contributed to customer satisfaction, so the work environment related to weather conditions needs to get attention or solutions to improve services to meet customer satisfaction, and this needs to pay attention to the location of the Community Health Center services in Probolinggo Regency, which is close to the highway.